On the optimal cathode catalyst layer for polymer electrolyte fuel cells: Bimodal pore size distributions with functionalized microstructures - García-Salaberri, Pablo A.; Sánchez-Ramos, Arturo; Das, Prodip K. (Frontiers in Energy Research, 2022)
A high understanding and advancement have been achieved in the design of proton exchange fuel cells (PEFCs) since the development of thin-film catalyst layers (CLs). However, the progress has slowed down in the last decade due to the difficulty in reducing the Pt loading, especially of the cathode CL, while preserving high stack performance. This situation poses a barrier to the widespread commercialization of fuel cell vehicles, where high performance and durability are needed at a reduced cost. Exploring the limits of the technology is necessary to adopt successful strategies that can allow a definitive development of PEFCs in the automotive industry. In this work, a numerical model of an optimized cathode CL is presented, which combines a multiscale formulation of mass and charge transport at the nanoscale (10 nm) and the layer scale (1 μ m). The effect of exterior oxygen and ohmic transport resistances are incorporated through mixed boundary conditions. The optimized CL features a vertically aligned geometry of equally spaced ionomer pillars, which are covered by a thin nanoporous shell. The surface of cylindrical nanopores is catalyzed with a Pt skin (atomic thickness), so that triple phase points are provided by liquid water. The results show the need to develop thin CLs with bimodal pore size distributions and functionalized microstructures to maximize the utilization of water-filled catalyzed nanopores where oxygen transport is facilitated compared with ionomer thin films. Proton transport across the CL must be assisted by low-tortuosity ionomer domains, providing highways for proton transport. Secondary pores as large as possible are beneficial to facilitate the distribution of oxygen in the CL and the removal of water. Ultimate targets set by the U.S. Department of Energy and other governments can be achieved by an optimization of the CL microstructure with a high electrochemical surface area, a reduction of the oxygen transport resistance from the channel to the CL, and an increase of the catalyst activity (or maintaining a similar activity with Pt alloys). Carbon-free supports (e.g., polymer or metal) are preferred to avoid corrosion and enlarge durability.